Mechanisms of Impaired Erythropoiesis in Sepsis - E. N. Barkova; V. V. Kuznetsov; Ye. V. Zhdanova; L. F. Balabanova; O. G. Sivkov; Ye. V. Nazarenko (Общая реаниматология, 2008)
Objective: to determine the mechanisms responsible for impairments in the space-time organization of erythropoiesis (SPOE) in experimental sepsis. Materials and methods. The diurnal changes in the titer of erythropoietin, the content of red blood cells, and their distribution by volume, the peripheral blood levels of hemoglobin and reticulocytes, life span, the production of erythrocytes, malonic dialdehyde (MDA), the statokinetic erythroid cell index, and bone marrow 59Fe incorporation were studied in 240 Wistar rats with multimicroial sepsis and 80 intact animals. Results. In sepsis, SPOE desynchronism was found to be due to increases in MDA and in the population of microcytes with shorter life span. The maximum duration was increased for erythropoiesis and decreased for erythrocytic production with the decreased peripheral blood level of ery-throcytes and hemoglobin. The progressive rise in the titer of erythropoiesis was accompanied by decreases in the statoki-netic index and bone marrow 59Fe incorporation with a simultaneous increase in the population of microcytes and with a reduction in the life span of erythrocytes. Conclusion. Endotoxicosis was established to play the leading role in the mechanisms of SPOE desynchronism. Activation of lipid peroxidation in the red blood cell membranes enhances their rigidity, by initiating the development of anemia and microcirculatory disorders. The decreases in erythrocytic production, statokinetic index, and bone marrow 59Fe incorporation with an inadequately high titer of erythropoiesis suggest the inhibition of ery-thropoietin-dependent processes in the target cells, which promotes the progression of septic anemia. Key words: bio-rhythms, erythropoiesis, erythropoietin, anemia, sepsis.